Effects of serotonin through serotonin1A and serotonin4 receptors on inhibition in the guinea-pig dentate gyrus in vitro - Bijak, Maria; Misgeld, Ulrich (Neuroscience, 1997)
The role of serotonin1A and serotonin4 receptors in the modulation of synaptic inhibition in the dentate gyrus of guinea-pig hippocampal slices was studied. The effects of serotonin (5-hydroxytryptamine) on hilar neurons and on inhibitory postsynaptic potentials in granule cells were compared using intracellular recording in the presence of glutamatergic receptor antagonists. On the basis of electrophysiological properties hilar neurons were classified as type I neurons (presumably inhibitory) and type II neurons (presumably excitatory). Serotonin hyperpolarized a proportion of type I hilar neurons (60%) and decreased their input resistance through activation of a K+-conductance. This effect was mediated by serotonin1A receptors since it was mimicked by the selective serotonin1A receptor agonist (±)-8-hydroxy-dipropylaminotetralin hydrobromide and blocked by the selective serotonin1A receptor antagonist (+) WAY 100135. In some type I hilar neurons (40%) neither serotonin nor (±)-8-hydroxy-dipropylaminotetralin hydrobromide induced a membrane hyperpolarization. Instead, serotonin induced an excitatory response, depolarizing the cells and blocking the slow afterhyperpolarization. Similar effects were seen in all hilar neurons after blockade of serotonin1A receptors. They were mimicked by the serotonin4 receptor agonist zacopride. Serotonin induced either decreases or increases in the frequency of spontaneous GABAA receptor-mediated inhibitory postsynaptic potentials in granule cells via activation of serotonin1A and of serotonin4 receptors, respectively. 4-aminopyridine-evoked GABAB receptor-mediated inhibitory postsynaptic potentials were inhibited by serotonin via activation of serotonin1A receptors. However, after blockade of serotonin1A receptors, serotonin increased the frequency of GABAB-inhibitory postsynaptic potentials through the activation of serotonin4 receptors. We conclude that a proportion of inhibitory neurons in the dentate area does not express serotonin1A receptors and is excited by serotonin. Other inhibitory neurons express serotonin1A receptors and are inhibited by serotonin.
Im Text sind "1A" und "4" tiefgestellt
Elektronische Reproduktion der Druck-Ausgabe
Online 13 February 1998
Gesehen am 27.04.2021